2012
DOI: 10.2478/s11535-012-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in the effect of dietary cholesterol in rats

Abstract: Male and female rats were fed diets supplemented with cholesterol and palm fat at 10 and 50 g/kg, respectively; serum, hepatic tissue and faeces were analysed. Cholesterol supplementation significantly increased serum and hepatic cholesterol both in male and female rats. Male and female rats fed the cholesterol-containing diet differed significantly in serum cholesterol concentration (2.48 µmol/mL vs 2.92 µmol/mL), concentration of serum triacylglycerols, but not in hepatic cholesterol concentration. The serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, it was shown that different physiological conditions such as gender and age could affect a dysregulation in brain cholesterol metabolism [22,23]. In addition, cholesterol concentration in serum significantly differed in male and female rats fed the cholesterol-containing diet [24]. Thus, further experiments will be needed to compare the effect of a high-cholesterol diet on PLCβ1 expression and PIP 2 levels by gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that different physiological conditions such as gender and age could affect a dysregulation in brain cholesterol metabolism [22,23]. In addition, cholesterol concentration in serum significantly differed in male and female rats fed the cholesterol-containing diet [24]. Thus, further experiments will be needed to compare the effect of a high-cholesterol diet on PLCβ1 expression and PIP 2 levels by gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA isolation and real-time PCR assay were performed as described previously (Marounek et al 2012). Briefly, total RNA was extracted from the liver tissue using an RNeasy Mini Kit (Qiagen, USA), reverse transcribed, and PCR was performed using the QuantiTect SYBR Green RT-PCR Kit (Qiagen, USA).…”
Section: Rna Isolation and Real-time Pcr Assaymentioning
confidence: 99%
“…Analyses of the feed were performed as described previously (Marounek et al 2012). The serum levels of total cholesterol, LDL cholesterol, triacylglycerols, and aminotransferases were determined using commercial kits supplied by Erba-Lachema, Ltd. (Brno, Czech Republic).…”
Section: Chemical Analysesmentioning
confidence: 99%